Pendampingan Pasien Tuberkulosis Resisten Obat (TBC-RO) Melalui Strategi Komunikasi Interpersonal Organisasi Mantan Pasien - Khuswatun Hasanah; Virginia Ayu Sagita (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2020)
AbstractThis study aims to examine the communication strategies carried out by the organization of former drug resistant tuberculosis patients Multidrug-Resistant Tuberculosis (MDR-TB) in assisting MDR-TB patients, both related to treatment, access to services, and about social impacts during treatment. As an innovation that was born in collaboration with the TB Sub Directorate of the Ministry of Health together with the Indonesia Challenge TB (CTB), the organization of ex-patients plays an important role in providing assistance. Because the treatment for MDR-TB patients is not easy in terms of the length of the treatment period, side effects of treatment, access to services, to other social problems. The former patient organization is present as a group that has undergone MDR-TB treatment periods so that the experience of delivering MDR-TB patients who are on medication has the same perception and motivation related to healing. The method used is a qualitative descriptive approach. Data obtained through observation, in-depth interviews (indepth interview), and documentation of all patient organization activities supported by CTB in 6 provinces in Indonesia. The results showed that through the similarity of fields of experience, the accompanying messages conveyed by patient organizations were channeled effectively. This is also supported by the interpersonal strategy of the organization of the former patient who plays himself as a peer educator in providing assistance and motivation for treatment. The communication is carried out by door to door (home visit), hospital visits, and through focus group discussions. This study also confirms the theory of Message Design Logic by Barbara O'Keefe that with the Rhetorical Message Design Logic, the message delivered is emphasized to achieve its goals not just the occurrence of response or reciprocity. In this case, supported by a shared experience, the motivation to complete treatment for TB patients will be more effective and get a good response.Keywords: Tuberculosis, MDR-TB, Interpersonal Communication, Field of ExperienceAbstraksiPenelitian ini bertujuan mengkaji strategi komunikasi yang dilakukan oleh organisasi mantan pasien tuberkulosis resisten obat (TBC-RO) dalam melakukan pendampingan terhadap pasien TBC-RO, baik terkait pengobatan, akses layanan, maupun perihal dampak sosial semasa pengobatan. Sebagai inovasi yang dilahirkan atas kolaborasi Sub Direktorat TBC Kementerian Kesehatan bersama dengan Challenge TB (CTB) Indonesia, organisasi mantan pasien memegang peranan penting dalam melakukan pendampingan. Pasalnya, pengobatan bagi pasien TBC-RO tidak mudah dari sisi lamanya jangka waktu pengobatan, efek samping pengobatan, akses layanan, hingga masalah sosial lainnya. Organisasi mantan pasien hadir sebagai kelompok yang pernah menjalani masa-masa pengobatan TBCRO sehingga pengalaman mengantarkan pasien TBC-RO yang sedang dalam pengobatan memiliki persepsi dan motivasi yang sama terkait kesembuhan. Metode yang digunakan adalah pendekatan deskriptif kualitatif. Data diperoleh melalui observasi, wawancara mendalam (indepth interview), dan dokumentasi dari segala kegiatan organisasi pasien dukungan CTB di 6 provinsi di Indonesia. Hasil penelitian menunjukkan bahwa melalui adanya kesamaan field of experience, pesan pendampingan yang disampaikan oleh organisasi pasien tersalurkan dengan efektif. Hal ini didukung pula oleh strategi interpersonal organisasi mantan pasien yang memerankan diri sebagai peer educator dalam memberi pendampingan dan motivasi pengobatan. Adapun komunikasi tersebut dilakukan secara door to door (home visit), kunjungan ke rumah sakit, dan melalui diskusi kelompok terarah. Penelitian ini sekaligus mengonfirmasi teori Message Design Logic oleh Barbara O’Keefe bahwa dengan gaya komunikasi logika desain pesan retorika, pesan yang disampaikan ditekankan untuk mencapai tujuannya bukan sekadar hanya terjadinya respon atau timbal balik saja. Dalam hal ini, didukung oleh kesamaan pengalaman maka motivasi menuntaskan pengobatan bagi pasien TBC-RO akan lebih efektif dan mendapatkan respon yang baik.Kata Kunci: Tuberkulosis, TBC-RO, Komunikasi Interpersonal, Field of Experience